Exploring Blockchain and AI in Digital Banking: A Literature Review on Transactions Enhancement, Fraud Detection, and Financial Inclusion - Pramudito, Dendy; Na’am, Jufriadif; Ernawan, Ferda (Sistemasi: Jurnal Sistem Informasi, 2025)
This paper explores the integration of Blockchain and Artificial Intelligence (AI) in the realm of digital banking, focusing on enhancing transaction efficiency, preventing fraud, and promoting financial inclusion. Utilizing a literature review methodology, this study synthesizes existing research to identify the synergistic effects of these two transformative technologies. Blockchain offers a decentralized, secure framework for transactions, while AI enhances data analysis and decision-making capabilities. The findings reveal that the combined application of Blockchain and AI can significantly streamline banking operations, reduce the incidence of fraud through advanced predictive analytics, and extend financial services to underserved populations. A comparison followed on case studies of successful digital banks that e taken advantage of AI and Blockchain technologies. In order to validate the results, industry experts and banking professionals were interviewed qualitatively to find out on the one hand where the opportunities lie and on the other where the challenges are when doing this implementation. Furthermore, the research highlights the challenges and limitations of implementing these technologies, including regulatory hurdles and the need for robust cybersecurity measures. By addressing these issues, financial institutions can leverage Blockchain and AI to create a more secure, efficient, and inclusive banking environment. This study not only fills a critical research gap but also provides practical recommendations for banking practitioners and policymakers. Ultimately, the integration of Blockchain and AI is poised to redefine digital banking, ensuring that technological advancements contribute to a more equitable financial landscape.